Konsep logik Muhammad bin Yusuf al-Sanusi: Kajian terhadap Mukhtasar fi ‘Ilm al-Mantiq /Nurfarzana Nizam - Nurfarzana , Nizam (2022)
Logic which is also known as “ilmu mantik” in Islamic tradition of knowledge is an intellect rule of thinking. Muḥammad bin Yūsuf al-Sanūsī (m.895H), an Ashāʻirah theological figure has used argumentation via naqlī and ‘aqlī as the source of evidence in the study of 20 attributes of Allah (Sifat 20). Thus, the burhān argumentation in Islamic creed is the proof of al-Sanūsī’s mastery in science of logic. Therefore, this study was conducted to analyse the logic work by al-Sanūsī, which is Mukhtaṣar fi ʻIlm al-Manṭiq. This study has focused on Mukhtaṣar because this work has the potential in the tradition of Islamic logical thinking and this study has started with going through al-Sanūsī’s background and his contributions in knowledge, especially in logical thinking. As for the data collection, it has been done using documentation methods and analysed through textual content analysis and historical methods based on the qualitative research design. As the result, this study has identified five main theories, which are the reference theory (al-dalālah), the utterance theory (al-lafẓ), the definitions theory (al-taʻrīfāt), the proposition theory (qaḍāyā) and the syllogism theory (al-qiyās). These theories which had formed al-Sanūsī logical concept is analysed based on the basic epistemology contemporary Islamic logical thinking that encompassed the inclusion of the subject (al-maddah) and format (al-ṣūrah). Finally, this study has discussed about the aspect of application and concept practicality according to al-Sanūsī’s logic with a few prospects and the challenges towards contemporary Islamic logical thinking. Lastly, this study also found that it is crucial to update the structure and the content of Mukhtaṣar to fulfil the need of contemporary Islamic logical thinking in facing the false thoughts. Meanwhile for the enrichment of terminological science of logic, this study has listed the al-Sanūsī logical terms in Mukhtaṣar fi ʻIlm al-Manṭiq.